"Partial duplication of lower lip and hemimandible" A rare case - Bibhuti Bhusan Nayak; Nilamani Mohanty (Indian Journal of Plastic Surgery)
Duplication of mandible and lower lip is a very rare congenital entity. We report an extremely uncommon case of Congenital Duplication of Lower lip and Mandible in a 3 year old girl, who was treated surgically in a single stage for correction of both lip and mandible. This was a commissure preserving single staged procedure. The Surgical procedure, the problems related to this anomaly and the embryology are discussed.